2005
DOI: 10.1093/humrep/dei236
|View full text |Cite
|
Sign up to set email alerts
|

The effect of chilling on membrane lipid phase transition in human oocytes and zygotes

Abstract: Zygotes show a higher resistance to chilling injury compared to oocytes at different developmental stages; this might explain the relatively poor survival rates of cryopreserved human oocytes and indicates the necessity to adjust the cryopreservation protocols in order to minimize cryoinjury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
79
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(81 citation statements)
references
References 41 publications
2
79
0
Order By: Relevance
“…Undoubtedly, the permeability of immature oocytes to cryoprotectant agents depends not only on their membrane lipid composition [51] and cortical microfilament network [52], but also on the presence of a somatic vestment. However, studies on this subject are not consistent.…”
Section: Oocyte-cumulus Cell Contact and Interactionmentioning
confidence: 99%
See 3 more Smart Citations
“…Undoubtedly, the permeability of immature oocytes to cryoprotectant agents depends not only on their membrane lipid composition [51] and cortical microfilament network [52], but also on the presence of a somatic vestment. However, studies on this subject are not consistent.…”
Section: Oocyte-cumulus Cell Contact and Interactionmentioning
confidence: 99%
“…It is reported that the oolemma of GV-stage oocytes contains high aquaporin [51]. In the plasma membrane of mature oocytes there are elevated concentration of saturated fatty acids (79,22 %) and a content of polyunsaturated fatty acids of 6,5 % [61].…”
Section: Oolemmamentioning
confidence: 99%
See 2 more Smart Citations
“…With the exception of an analysis of Van Blerkom and Davies published in the mid-nineties [21], further evidence on the ultrastructure of frozen-thawed oocytes has been gained only recently. Ultrastructural alterations involving the cortical granules (CG), ZP, organelle associations, and ooplasm were reported in coincidence with the application of particular dehydration and rehydration conditions [19,[22][23][24] or possibly specific CPAs [23], suggesting that TEM can represent a first line investigative tool.…”
Section: Introductionmentioning
confidence: 99%